2009
DOI: 10.1080/01635580802395717
|View full text |Cite
|
Sign up to set email alerts
|

Screening for In Vitro and In Vivo Antitumor Activities of the MushroomAgaricus Blazei

Abstract: We have investigated the in vitro antitumor activity of the mushroom Agaricus blazei Murill on human cancer cell lines as well as its potential anticancer activity in a model of rat colon carcinogenesis. The in vitro anticancer analysis was performed using 9 human cancer cell lines incubated with organic and aqueous extracts of A. blazei. Antitumor activity was observed with the dichloromethane/methanol and hexanic extracts of A. blazei at 250 mu g/ml for all cancer cell lines tested. No antiproliferative/cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…This fungus usually serves as health-care food and alternative medicine by patients to treat common serious diseases like atherosclerosis, hepatitis, hyperlipidaemia, diabetes mellitus, dermatitis and cancer [1][2][3]. Its chemical components have been widely studied, including agaritine [4], steroids [5], lipids [4], lectin [6], and various polysaccharides [4,7]. This fungus is rich in polysaccharides that have shown significant effects in treating and preventing cancer [8].…”
Section: Introductionmentioning
confidence: 99%
“…This fungus usually serves as health-care food and alternative medicine by patients to treat common serious diseases like atherosclerosis, hepatitis, hyperlipidaemia, diabetes mellitus, dermatitis and cancer [1][2][3]. Its chemical components have been widely studied, including agaritine [4], steroids [5], lipids [4], lectin [6], and various polysaccharides [4,7]. This fungus is rich in polysaccharides that have shown significant effects in treating and preventing cancer [8].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of this effect is possibly via action of PSK on a toll-like receptor initiating a signaling cascade involving T helper 1 cells which induce IL-2 and IFN-c and then activate natural killer cells. This sequence of signaling cascades has recently been described in the modulation of innate immunity of Agaricus blazei (Ab) (Hetland et al, 2011), although intake of 5% Ab over 4 weeks by male Wistar rats did not confirm chemopreventive activity on the initiation stage of rat colon carcinogenesis (Ziliotto, Barbisan, & Rodrigues, 2008;Ziliotto, Pinheiro, Barbisan, & Rodrigues, 2009).…”
Section: Colorectal/colon Cancer Studiesmentioning
confidence: 98%
“…Later, chemically induced carcinogenesis has been used as experimental tumor models in rodents for both hepatocarcinogenesis and colon carcinogenesis studies [16,17] on possible beneficial effects of AbM extracts. The former study demonstrated hepatoprotective effect of orally administered A .…”
Section: Introductionmentioning
confidence: 99%
“…The former study demonstrated hepatoprotective effect of orally administered A . blazei extract [16], and the latter [17] showed tendency to reduced dysplastic aberrant crypt formation in colon but no difference in colon tumor incidence after A . blazei ingestion [17].…”
Section: Introductionmentioning
confidence: 99%